PRACTICE OF FORMATION OF PROFESSIONAL COMMUNICATIVE COMPETENCE OF THE FUTURE TRANSLATORS IN THE PROCESS OF PROFESSIONAL TRAINING - Z.F. Pidruchna (Academy of Cognitive and Natural Sciences, 2008)
The content of the educational subject interpretation is analysed in this article; the practice of the process of the professional communicative competence formation in the system of the future interpreter's preparation is also characterized here.